Predictors of women’s depression during postpartum period - Zamalijeva, O.; Jusienė, R. (Psichologija, 2010)
Approximately 20 percent of women suffer from postpartum depression after childbirth, which, in turn, negatively affects women’s well-being, child’s development and interactions with the child and family. Risk factors, which most significantly influence postpartum depression, have been analyzed by numerous researchers, seeking to make it possible to predict and identify women at risk before the onset of symptoms. Nevertheless, the data obtained is inconclusive and research results are contradictory. The most inconclusive results are those related to demographic and socioeconomic characteristics and their impact on depressive symptoms during postpartum period. Moreover, there are inconsistencies in conclusions concerning social support, pregnancy and delivery-related factors, stressful life events, emotional and physical health and their influence on postpartum depression. The goal of this research is to identify demographic, social, psychological and health related variables that could reliably predict women’s depression half year after delivery. This research is prospective and longitudinal, participants were interviewed at several assessment points – during pregnancy, the first month and half a year postpartum. The complete data about 66 women are analyzed in this article. The results of structural equation modeling (SEM), indicate that the only significant predictor of women’s depressive symptoms during postpartum period, having direct effect, is depression during pregnancy, i.e. women who report more depressive symptoms during pregnancy are significantly more likely to be depressed during postpartum period. Women who rated their subjective readiness for motherhood as lower, also with high anxiety concerning delivery, poor quality of relationship with a partner, and who reported more stressful life events, as well as primiparous women are at greater risk postpartum depression; however these variables and depressive symptoms during postpartum period are not directly related. The readiness for motherhood and anxiety concerning delivery predicts depression during pregnancy. The quality of relationships with partner, in turn, predicts both readiness for motherhood and anxiety concerning delivery. Finally, the readiness for motherhood could also be predicted by stressful life events and primiparity. The results of our study support the necessity of psychological interventions during the pregnancy in order to prevent postpartum depression.